The persona lifecycle keeping people in mind throughout product design - Pruitt, John.; Adlin, Tamara (Amsterdam ; Boston : Elsevier : Morgan Kaufmann Publishers, an imprint of Elsevier, 2006)
"The Persona Lifecycle addresses the "how" of creating effective personas and using those personas to design products that people love. It doesn't just describe the value of personas; it offers detailed techniques and tools related to planning, creating, communicating, and using personas to create great product designs. Moreover, it provides rich examples, samples, and illustrations to imitate and model. Perhaps most importantly, it positions personas not as a panacea, but as a method used to complement other user-centered design (UCD) techniques including scenario-based design, cognitive walkthroughs and user testing"--Resource description p.
The next frontier for user-centered design : making user representations more usable -- The persona lifecycle : a framework for the persona approach -- Phase 1: Family planning (planning a persona effort) -- Phase 2: Conception & gestation (creating personas) -- Phase 3: Birth & maturation (launching and communicating personas) -- Phase 4: Adulthood (using personas) -- Phase 5: Lifetime achievement and retirement (ROI and reuse of personas) -- Contributed chapters: Users, roles and personas / by Larry Constantine -- Storytelling and narrative / by Whitney Quesenbery -- Reality and design maps / by Tamara Adlin & Holly Jamesen -- Marketing versus design personas / by Bob Barlow-Busch -- Why personas work : the psychological evidence / by Jonathan Grudin -- Appendix A: G4K organizational archetype and sample persona -- Appendix B: Example personas from real projects -- Appendix C: Sample image release form.
Includes bibliographical references (p. 693-705) and indexes.
Keywords: Product management; New products; Research, Industrial; Electronic books